PENDEKATAN SISTEM DALAM MEMECAHKAN MASALAH PERKAWINSN POLIGAMI TANPA IZIN PENGADILAN - Sulaiman, Eman (Jurusan Syariah dan Ekonomi Islam Institut Agama Islam Negeri (IAIN) Parepare, 2014)
This article outlines the system approach in solving the problem without court permission polygamous marriage with normative and sociological approaches. The results obtained by the understanding that the discussion of problem solving polygamous marriage without court permission, not only handled / disconnected by using a normative approach, but must be completed / decided by other considerations, such as solving / conflict with empirical and philosophical approach as a complete system, so that a decision completed / solved by law enforcement and justice (judge) promoting a sense of justice for the people / society. Mistake in making decisions, will lead to bad consequences in the lives of families / households and communities.